2018
DOI: 10.1038/s41389-018-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Otx2 promotes granule cell precursor proliferation and Shh-dependent medulloblastoma maintenance in vivo

Abstract: The developmental gene OTX2 is expressed by cerebellar granule cell precursors (GCPs), a cell population which undergoes massive expansion during the early postnatal period in response to sonic hedgehog (Shh). GCPs are thought to be at the origin of most medulloblastomas, a devastating paediatric cancer that arises in the developing cerebellum. OTX2 is overexpressed in all types of medulloblastomas, except in Shh-dependent type 2 medulloblastomas, although it has GCPs as cell-of-origin. This has led to the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…3d ). Otx2 encodes orthodenticle homeobox 2, a transcription factor that shapes the morphogenesis of the cerebellum through controlling the proliferation of postnatal granule cell precursors 43 . The middle GCL sublayer is enriched with the marker gene Cbln3 , which is predominantly expressed in mature granule cells that have ceased division and finished migration into the GCL 44 .…”
Section: Resultsmentioning
confidence: 99%
“…3d ). Otx2 encodes orthodenticle homeobox 2, a transcription factor that shapes the morphogenesis of the cerebellum through controlling the proliferation of postnatal granule cell precursors 43 . The middle GCL sublayer is enriched with the marker gene Cbln3 , which is predominantly expressed in mature granule cells that have ceased division and finished migration into the GCL 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the outer GCL sublayer is adjacent to the Purkinje cell layer and is enriched with the marker gene Otx2 (Figure 3g). Otx2 encodes orthodenticle homeobox 2, a transcription factor that shapes the morphogenesis of cerebellum through controlling the proliferation of postnatal granule cell precursors 40 . The middle GCL sublayer is enriched with the marker gene Cbln3 , which is predominantly expressed in mature granule cells that have ceased division and finished migration into the GCL 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin accessibility is altered in medulloblastoma, where histone modifications may allow for increased OTX2 expression, and hence a positive feedback loop for OTX2 ( Wortham et al, 2014 ). Recent studies have also shown OTX2 is potentially required for tumor proliferation in the SHH group, although not necessarily for tumor formation ( El Nagar et al, 2018 ). In Group 3 medulloblastoma, OTX2 represses PAX3 and PAX6.…”
Section: Selected Transcription Factors Encoded By Homeobox Genesmentioning
confidence: 99%